Metode Penegakan Etika Bisnis Islam dalam Dunia Usaha dan Korporasi - Hamzah Tacong (CV. Kurnia Grup, 2026)
The increasingly competitive business environment requires companies to focus not only on profit generation but also on implementing ethical principles in every business activity. Various issues, including corruption, manipulation, unfair business competition, and the lack of corporate social responsibility, highlight the importance of Islamic business ethics in establishing corporate governance with integrity. This study aims to analyze the methods of implementing Islamic business ethics in business organizations and corporations, identify the challenges encountered in its implementation, and examine its impact on corporate sustainability. This study employed a library research method with a descriptive qualitative approach. Data were collected from the Qur'an, Hadith, books, scientific journal articles, and other relevant academic sources and analyzed using content analysis. The findings indicate that the implementation of Islamic business ethics can be achieved through education, the application of corporate codes of ethics, supervision by the Sharia Supervisory Board, sharia audits, the development of an Islamic work culture, the implementation of Corporate Social Responsibility (CSR), and the strengthening of monitoring and law enforcement systems. These methods enhance customer trust, corporate reputation, competitiveness, and business sustainability.